5x – 3y = 13
4x – 3y = 11
Can someone tell me if I did this right.
I multiply the first equation by -1 to get (-5x + 3y = -13)
-5x + 3y = -13
4x - 3y = 11
-1x = -2
x= 2
When I try to solve for "y" I get y =-1 so is that right?
5x – 3y = 13
4x – 3y = 11
Can someone tell me if I did this right.
I multiply the first equation by -1 to get (-5x + 3y = -13)
-5x + 3y = -13
4x - 3y = 11
-1x = -2
x= 2
When I try to solve for "y" I get y =-1 so is that right?
you know, you can see for yourself that your answers were correct.
you could plug in the values you got for x and y on the left side of BOTH equations and see if you get the answers on the right.
i say both, because i have seen solutions where the answers work for one equation but not the other--and so, the system was not solved